From Contextual to Actual Approach: Towards a Paradigm Shift in Interpreting the Qur’an - Muttaqin, Ahmad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2021)
This article examines the paradigm shift in the interpretation of the Qur'an. The main thesis in writing is that there is a paradigm shift in the approach to interpretation of contextualist figures and the need for a new paradigm to actualize interpretations. Therefore, this paper presents an explanation of how the construction and paradigm shift in the interpretation of contextualist figures; why the paradigm shift of contextual interpretation occurs, and what are the implications of this shift in the principles of the new paradigm of interpretation. This study is a literature review. As a sample of the data, there are five contextualist thinkers studied, namely Fazlur Rahman (Pakistan-America), Nasr Hamid Abu Zayd (Egypt-Netherlands), Farid Esack (South Africa), Abdullah Saeed (Maldives-Australia), and Sahiron Syamsuddin (Indonesia). Data were analyzed using comparative-relational analysis. This study concludes that the paradigm shift in interpretation cannot be separated from the influence of the sociopolitical and cultural context of each country. The paradigm of interpretation has shifted from a contextual approach to an actual-context approach. The latter approach emphasizes more on actual issues and solutions to national and state issues. This study also proposes a thesis that, different from the contextual paradigm that emphasizes the context of the Qur'an as a medium for understanding the text of the Qur'an, the actual-context approach emphasizes the text of the Qur'an as a medium for understanding the context of the Qur'an. It is because the text is actually a cultural representation of the reality of the time of revelation.   Artikel ini mengkaji pergeseran paradigma (paradigm shift) dalam penafsiran al-Qur’an. Tesis utamanya adalah ada pergeseran paradigma dalam pendekatan penafsiran tokoh kontekstualis dan perlunya paradigma baru untuk mengaktualkan panafsiran. Untuk itu, tulisan ini menghadirkan penjelasan bagaimana konstruksi dan pergeseran paradigma penafsiran tokoh kontekstualis; mengapa pergeseran paradigma penafsiran kontekstual terjadi, serta apa implikasi pergeseran tersebut dalam prinsip paradigma penafsiran yang baru. Studi ini merupakan kajian kepustakaan. Sebagai sampel data, ada lima pemikir kontekstualis yang dikaji, yaitu Fazlur Rahman (Pakistan-Amerika), Nasr Hamid Abu Zayd (Mesir-Belanda), Farid Esack (Afrika Selatan), Abdullah Saeed (Maladewa-Australia), dan Sahiron Syamsuddin (Indonesia). Data dianalisis menggunakan analisis komparatif-relasional. Penelitian ini menyimpulkan bahwa pergeseran paradigma penafsiran tidak terlepas dari pengaruh konteks sosiopolitik dan kultural negara masing-masing. Paradigma penafsiran mengalami pergeseran dari pendekatan kontekstual ke pendekatan aktual. Pendekatan yang terakhir lebih menekankan pada isu aktual dan solusi atas persoalan kebangsaan dan kenegaraan. Penelitian ini juga mengajukan tesis bahwa jika dalam paradigma kontekstual lebih menekankan konteks al-Qur’an sebagai media untuk memahami teks al-Qur’an, pendekatan aktual lebih menekankan teks al-Qur’an sebagai media untuk memahami konteks al-Qur’an, karena teks sejatinya merupakan representasi kultural atas realitas masa pewahyuan.